Integrated principles of zoology - Hickman, Cleveland P., Jr.; Keen, Susan L.; Eisenhour, David J.; Larson, Allan; I'Anson, Helen (New York: McGraw Hill, 2024)
"The overall organization of this text has proven to work well to help students understand the content. Distinctive features, especially the emphasis on principles of evolution and zoological science, have been strengthened. To aid in student learning, several pedagogical features have been retained: opening chapter prologues drawn from the chapter's theme; chapter summaries and review questions to aid in comprehension and study; concise and visually appealing illustrations; chapter notes and essays that offer interesting sidelights to the narrative; literature citations; and an extensive glossary providing pronunciations, derivations, and definitions of terms used in the text"--
Part One. -- Introduction to living animals -- Part Two. -- Continuity and evolution of animal life -- Part Three. -- Diversity of animal life -- Part Four. -- Activity of life -- Part Five. -- Animals and their environments.
Includes index.
Keywords: Zoology